The difference between live satellite TV channel broadcasting and live Internet TV channel (Eurasian Journal of Media and Communications, 2022)
According to the digital transformation that the world is witnessing today, it has become necessary to understand the way in which live broadcasting of TV channels via satellite and the Internet works. Therefore, the first aim of this study is to reveal the complex processes of video rendering and to know the difference between live broadcasting of TV channels via satellite and via the Internet, and the types of broadcasting for each of them. Since each kind of broadcast has its advantages and disadvantages, the second aim is to know the advantages and disadvantages of both live broadcasting via satellite and live broadcasting via the Internet. People have become accustomed to it, but this coexistence does not mean that we use media and communication media in the same form and pace due to the technical problems that accompany its use, while research recommends that broadcasting via the Internet constitutes the emergence of a new style of media multi-use and, consequently, the emergence of new media professionals, programs, and a wide audience that need attention and support, as well as the expansion of studies that include these types